Corrections for Pumped SBE 41CP CTDs Determined from Stratified Tank Experiments - Martini, Kim I.; Murphy, David J.; Schmitt, Raymond W.; Larson, Nordeen G. (Journal of atmospheric and oceanic technology, 2019)
Sea-Bird Scientific SBE 41CP CTDs are used on autonomous floats in the global Argo ocean observing program to measure the temperature and salinity of the upper ocean. While profiling, the sensors are subject to dynamic errors as they profile through vertical gradients. Applying dynamic corrections to the temperature and conductivity data reduces these errors and improves sensor accuracy. A series of laboratory experiments conducted in a stratified tank are used to characterize dynamic errors and determine corrections. The corrections are adapted for Argo floats, and recommendations for future implementation are presented.